Comparison in knee osteoarthritis joint damage patterns among individuals with an intact, complete and partial anterior cruciate ligament rupture - Johnson, Victoria L.; Guermazi, Ali; Roemer, Frank; Hunter, David J. (International Journal of Rheumatic Diseases, 2017)
The aim of this study was to examine the difference in the pattern of articular damage in persons with either a partial anterior cruciate ligament (ACL) tear; a complete ACL tear or no ACL tear.Our study included 600 individuals (of the 600 individuals, 25 with a partial, 12 with a complete ACL tear and 563 with no ACL tear) from the progression sub-cohort of the Osteoarthritis Initiative. Individuals had a mean age of 61.8 years (range 45-79 years). Chi-square tests were used to compare the location of meniscal pathology, bone marrow lesions (BMLs) and regional cartilage morphology between individuals with a partial or complete ACL tear, as seen on magnetic resonance imaging, as well as to a control group of 563 knees.Individuals with either a complete or partial ACL tear displayed predominantly medial tibiofemoral damage. Individuals with complete ACL tears were more likely to have cartilage lesions in the lateral posterior tibia (P = 0.03) and the medial anterior femur (P = 0.008) as well as BMLs in the medial posterior tibia (P = 0.007). However, no significant difference in meniscal morphology was found in either compartment. Individuals with no history of knee trauma or ACL injury displayed predominantly medial tibiofemoral compartment damage.Individuals with prevalent ACL disruptions exhibited concomitant osteoarthritic changes in the medial tibiofemoral compartment, as seen on MRI. As the changes in joint tissues were predominantly located in the medial compartment, it is thought that these ACL tears may represent a manifestation of the overall disease process rather than the precipitant for osteoarthritis incidence.
EVALuna2:14695